The safety and efficacy of vosaroxin in patients with first relapsed or refractory acute myeloid leukemia - a critical review. Issue 6 (2nd June 2016) - Short, Nicholas J.; Ravandi, Farhad
ABSTRACT: Introduction : The outcomes of patients with relapsed or refractory acute myeloid leukemia (AML) are dismal, and effective treatment options in this patient population are therefore desperately needed. Vosaroxin is a first-in-class anticancer quinolone derivative that has shown promising activity in patients with relapsed or refractory AML. Areas Covered : Studies in relapsed/refractory AML, including a large randomized phase III trial, have shown improved response rates when vosaroxin was combined with cytarabine, which translated to prolonged survival in certain subsets of patients, including older patients. Given the encouraging results of vosaroxin in the relapsed/refractory setting, several studies are also evaluating vosaroxin in older patients with untreated AML who are not candidates for intensive chemotherapy. The results from clinical trials evaluating vosaroxin in both treatment naïve and relapsed/refractory AML will be reviewed. Expert Commentary : Vosaroxin has shown significant promise in the management of AML, especially in older patients with relapsed/refractory disease. As vosaroxin has been associated with increased toxicity in some studies, appropriate dosing and patient selection will be crucial to determine the future role of vosaroxin in AML.